Dermoscopic Assessment of Nail Alterations in Egyptian Patients with Alopecia Areata - Galal, Sara; Tiranly, Radwa; Pessar, Doaa; Elsadek , Hala (Dermatology Practical & Conceptual, 2026)
Introduction: Alopecia areata (AA) is an autoimmune disorder characterized by non-scarring hair loss. Hair and nails have many commonalities related to their development and structure and both can be involved in a range of disorders. Dermoscopy is a valuable noninvasive diagnostic tool that enhances clinical evaluation and treatment monitoring by detecting subtle nail changes not visible to the naked eye. Aim: The goals of this study were to assess the prevalence and types of various fingernail changes in patients with alopecia areata using dermoscopy and to compare the findings with those observed in healthy controls. Methods: A case-control study was conducted including 120 patients diagnosed with alopecia areata and 120 healthy individuals as controls. Dermoscopic examination of the fingernails was done for all participants. The severity of alopecia areata was evaluated using the Severity of Alopecia Tool (SALT) score. Results: Nail changes were observed in 78.3% of patients with alopecia areata, compared to only 14.2% in the control group, showing a statistically significant difference (P<0.05). The most frequent dermoscopic nail change was nail pitting (59%), followed by dry scales on the lateral nail fold (28.3%), scaly cuticle (18.3%), punctate leukonychia (17.5%), onychoschizia (14.2%), and longitudinal ridging (13.3%). There was a significant association between nail changes and disease severity, patient age, and alopecia areata duration. Conclusions: Nail changes are common in patients with alopecia areata and may serve as valuable prognostic indicators for disease severity.